Indoor Characterisation of a Photovoltaic/ Thermal Phase Change Material System - MCCORMACK, SARAH (My University, 2015)
Photovoltaic/ thermal (PV/T) systems integrate photovoltaic and solar thermal technologies and have the added advantage of producing both electrical and thermal energy simultaneously. This study has been carried out to investigate the performance of a PV/T phase change material (PCM) system under experimental climatic conditions. Electricity is generated by the PV during daylight hours and the heat produced is absorbed and stored in PCM. Water flows through a pipe network within the PCM and absorbs the stored heat in the PCM. In the PV/T-PCM system, water remained at a higher temperature for an extended period of time as well as shifting the time period of available heat when compared to the reference systems.
Keywords: Photovoltaic/ thermal systems; phase change material; thermal perfomance